Hydrocarbon accumulation period and process in Baobab area of Bongor Basin. (January 2020) - Dou, Lirong; Li, Wei; Cheng, Dingsheng
Abstract: The hydrocarbon reservoirs of Baobab area in the Northern Slope of the Bongor Basin in Chad, are very important petroleum exploration region in the basin. Baobab area could be divided into BS zone, BC zone and BN zone according to the tectonic distribution characteristics. All the three zones develop sandstone reservoirs, and the BC zone is mainly buried-hills reservoirs. Based on the analysis of the oil-source relationship of BS, BN and BC zone, the hydrocarbon accumulation period and adjustment process was investigated using a suite of hydrocarbon generation and expulsion history, tectonic thermal evolution history, GOI characteristics of fluid inclusions, microfluorescence determination and temperature measurement technology. The results show that crude oils of BS zone were sourced from BS zone source rock, oils of BN zone from BN zone source rock, and oil of BC zones from both of BS and BN source rocks. The history of hydrocarbon generation and expulsion history of source rock shows that the source rocks in BS zone matured earlier than the source rocks of BN. The hydrocarbon accumulation occurred in the early Late Cretaceous in BS zone, and in the middle Late Cretaceous in BN zone. The hydrocarbon accumulation period in the BC reservoirs was controlled by the hydrocarbon generation and expulsion history of source rock in BS and BN zones, which was a continuous process with different accumulation intensities during the Late Cretaceous. Due to the effects of tectonic events during Late Cretaceous, buried hill reservoirs of BC zone experienced the primary hydrocarbon accumulation of about 80-55 Ma and the secondary hydrocarbon accumulation at about 25 Ma. The reconstruction of buried-hill reservoirs in BC zone is obvious. The migration of crude oils from the ancient reservoir to the higher part of the Baobab structure along the faults and fractures due to tectonic inversion formed a new reservoir, and the oil-water contact became shallower about 357 m. Highlights: Analysis the oil-source relationship of BS zone, BC zone and BN zone. Hydrocarbon accumulation was a continuous process with two peak in BC zone. The reconstruction of buried-hill reservoir of BC zone is obvious.